2007
DOI: 10.1148/radiol.2422060029
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Airways with Three-dimensional Quantitative Thin-Section CT: In Vitro and in Vivo Validation

Abstract: This method enables accurate and reproducible measurement of WA and LA on reformatted CT sections perpendicular to the main axis of bronchi visible on thin-section CT scans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
81
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 27 publications
0
81
0
Order By: Relevance
“…In this study, the overall success rates for the extraction of segmental and subsegmental bronchi by this software were 92.9% (936/1 008) and 74.8% (754/ 1 008), respectively ( Table 2). One study has shown that 80.8% of third-generation bronchi and 72.5% of fourthgeneration bronchi were successfully identified in this way, in vivo [17]. Although it was not possible to perform an accurate comparison, owing to the differences among subjects and evaluation methods, it seemed that there was no large difference between these results.…”
Section: Three-dimensional Airway Lumen Volumetry In Pulmonary Emphysemamentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the overall success rates for the extraction of segmental and subsegmental bronchi by this software were 92.9% (936/1 008) and 74.8% (754/ 1 008), respectively ( Table 2). One study has shown that 80.8% of third-generation bronchi and 72.5% of fourthgeneration bronchi were successfully identified in this way, in vivo [17]. Although it was not possible to perform an accurate comparison, owing to the differences among subjects and evaluation methods, it seemed that there was no large difference between these results.…”
Section: Three-dimensional Airway Lumen Volumetry In Pulmonary Emphysemamentioning
confidence: 99%
“…One of the reasons for this might be that the luminal area/volume of emphysema patients tends to decrease. In fact, Montaudon et al [17] showed that the number of bronchi reconstructed by their software package decreased dramatically beyond the fifth generation (third-generation bronchi 80.8%; fourth generation 72.5%; fifth generation 37.7%; sixth generation 10.7%). Considering these findings, it seems that luminal area/volume is influenced by the extraction of bronchi.…”
Section: Three-dimensional Airway Lumen Volumetry In Pulmonary Emphysemamentioning
confidence: 99%
“…Subsequently, automated and semi-automated computer-based algorithms have been developed. The principles underlying these techniques include: threshold-based methods [18,28,29]; the full-width at half maximum (FWHM) distance [20,30]; score-guided erosion [18]; ''Laplacian of Gaussian'' filters to detect airway edges [9,31]; and algorithms based on idealised airway models [32,33]. These computer algorithms are based on tissue density measures rather than on arbitrary grayscale measures and have been discussed elsewhere in detail [17,34,35].…”
Section: Measuring Airway Dimensions From Ct Datamentioning
confidence: 99%
“…''Skeletonisation'' facilitates such reconstruction by segmenting the bronchial tree and connecting the resulting contiguous airway centrelines to form a branching tree-like structure ( fig. 3) [22,31,36,40]. Creation of an airway skeleton facilitates orderly exploration of the tracheobronchial tree and serves as a viewpoint trajectory for navigation during bronchoscopy [22].…”
Section: Measuring Airway Dimensions From Ct Datamentioning
confidence: 99%
“…These include partial volume averaging, the applied reconstruction kernel, the software used to make the measurements, the radiation dose and lung volume [13,14]. Labelling and categorising bronchi by generation and location are important, and are a further source of variation [31].…”
mentioning
confidence: 99%